Enhanced proton acceleration via Petawatt Laguerre–Gaussian lasers - Wenpeng Wang; Xinyue Sun; Fengyu Sun; Zhengxing Lv; K. Glize; Zhiyong Shi; Yi Xu; Zongxin Zhang; Fenxiang Wu; Jiabing Hu; Jiayi Qian; Jiacheng Zhu; et al. (Communications Physics)
Abstract High-energy, high-flux collimated proton beams with high repetition rates are critical for applications such as proton therapy, proton radiography, high-energy-density matter generation, and compact particle accelerators. However, achieving proton beam collimation has typically relied on complex and expensive target fabrication or precise control of auxiliary laser pulses, which poses significant limitations for high-repetition applications. Here, we demonstrate an all-optical method for collimated proton acceleration using a single femtosecond Laguerre–Gaussian (LG) laser with an intensity exceeding 1020 W/cm2 irradiating a simple planar target. Compared to conventional Gaussian laser-driven schemes, the maximum proton energy is enhanced by 60% (reaching ~35 MeV) and beam divergence is much reduced. Particle-in-cell simulations reveal that a plasma jet is initially focused by the hollow electric sheath field of the LG laser, then electrons in the jet are further collimated by self-generated magnetic fields. This process amplifies the charge-separation electric field between electrons and ions, leading to increased proton energy in the longitudinal direction and improved collimation in the transverse direction. This single-LG-laser-driven collimation mechanism offers a promising pathway for high-repetition, high-quality proton beam generation, with broad potential applications including proton therapy and fast ignition in inertial confinement fusion.